Real-Time Quaking-Induced Conversion Detection of Bovine Spongiform Encephalopathy Prions in a Subclinical Steer - Hwang, Soyoun (Front Vet Sci, 2018)
Bovine spongiform encephalopathy (BSE) belongs to a group of fatal prion diseases that result from the misfolding of the cellular prion protein (PrP(C)) into a pathogenic form (PrP(Sc)) that accumulates in the brain. In vitro assays such as serial protein misfolding amplification and real-time quaking-induced conversion (RT-QuIC) allow assessment of the conversion of PrP(C) to PrP(Sc). RT-QuIC can be used for the detection of prions in a variety of biological tissues from humans and animals. However, there is no such comparison of RT-QuIC data between BSE positive and presymptomatic cattle. Further, the current study assesses prion distribution in multiple brain regions of clinically ill or subclinical animals. Here, we compare RT-QuIC reactions seeded with brain samples collected from experimentally inoculated cattle that were clinically ill or subclinically affected with BSE. The results demonstrate RT-QuIC seeding in various brain regions of an animal with subclinical BSE despite being determined negative by immunohistochemistry. Bioassay of the subclinical animal and RT-QuIC of brainstem from inoculated knockout (PRNP(−)(/)(−)) cattle were used to confirm infectivity in the subclinical animal and determine that RT-QuIC reactions were not the result of residual inoculum, respectively. These results confirm that RT-QuIC is a highly sensitive prion detection assay that can detect prions in a steer prior to the onset of clinical signs of BSE.